Application of Ash Corrections to Analyses of Various Coals - A. C. Fieldner (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
A FORMER paper1 described in detail various methods of calculating coal analyses to obtain the composition and calorific value of the pure coal substance-that is, of the coal free from its mineral matter. The paper included a table showing calorific values of pure coal, as calculated from float-and-sink portions, by means of the Parr formula for "unit coal" and by the customary moisture-free and ash-free formula. A modification of the Parr formula was proposed, based on the assumption that one-half the sulfur present in coal occurs as pyritic sulfur and one-half as organic sulfur. In the published discussion of the paper Cady gave a table of results on a large number of Illinois coals as obtained by the Parr formula and the proposed modification thereof. The results obtained by Cady indicate that the Parr formula applies better to Illinois coals than does the modified formula proposed by Fieldner and Selvig. The present paper gives results obtained by applying the modified Parr formula to the analyses of the float-and-sink portions of the coals shown in the former paper, and results obtained by applying the Parr formula, the modified Parr formula, and the simple moisture-free and ash-free formula to various coals of the United States ranging in sulfur content from less than 1 per cent to more than 4 per cent sulfur. A graphic method of estimating the calorific value of pure coal and determin-ing the relation of the coal ash to the mineral matter of coal, as proposed by Stansfield and Sutherland,2 was applied to a number of coals, and the results are given herein.